Evaluation of a rail-travel simulator for elderly adults with cognitive disorders. The Grand-Via Project, a travel therapy pilot study. (November 2021) - Defouilloy, Isabelle; Ernecq, Julie; Froment, Jean-Christophe; Couvillers-Dek, Frédérique; Boutalha, Samir; Bloch, Frédéric
Abstract: Background and purpose: Travel therapy can reduce anxiety symptoms in elderly adults with cognitive disorders. The objective of this pilot study was to evaluate the use of a rail-travel simulator in this purpose. Materials and methods: The study was a prospective, single centre cohort survey. Our study population consisted of persons either from the nursing home, the cognitive and behavioural unit or the day-care centre of our university hospital. Participants were accompanied on a virtual trip using a film projection in a replica of train compartment. Participants were interviewed before and after each session using a short questionnaire developed by a multi-disciplinary team. Results: Forty-two participants performed sessions. While only 58.3% of the participants reported being relaxed before the session, this rate increased significantly to 87.5% by the end of the trip. A majority of participants gave their personal impressions and half of the group reported memories evoked by the experience. Conclusion: The majority of elderly persons who completed the virtual trip replied positively about the experience. We need now to confirm the efficacy of our simulator using a randomised controlled trial. Highlights: Our rail-travel simulator prototype enables the projection of a film in a replica of a train compartment. It significantly reduced anxiety and behavioural symptoms of elderly adults with cognitive disorders. Travel therapy can be effective on persons with cognitive disorders.